Once Again, is Openness Good for Growth? (IMF Working Papers; Working Paper, 2004)
Rodriguez and Rodrik (2000) argue that the relation between openness and growth is still an open question. One of the main problems in the assessment of the effect is the endogeneity of the relation. In order to address this issue, this paper applies the identification through heteroskedasticity methodology to estimate the effect of openness on growth while properly controlling for the effect of growth on openness. The results suggest that openness would have a positive effect on growth, although small. This result stands, despite the equally robust effect from growth to openness.